Manajemen Pengembangan Karakter Anak Usia Dini Melalui Kegiatan Parenting - Mustarsida, Ulyatul; Maarif, Muhammad Anas; Rusydi, Ibnu (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to describe and find out how the results of parenting activities in this institution are related to the development of the character of existing students. The management patterns carried out by the head of the school against parenting, as well as the obstacles and support that the institution has in developing the character of the child, are also the subject of this research. This research is conducted using qualitative research methods. Qualitative research methods are chosen because qualitative approaches serve to explore and understand the meaning of individuals or groups related to social problems that can later be used to interpret and gain an in-depth understanding of certain aspects of human beliefs, attitudes, or behavior. The subjects of the research are the head of the school as well as the head of the institute, parents, teachers, and students. To obtain the desired data, this research uses interview techniques, snowballing systems, documentation, and observations. The analysis is done using qualitative analysis. By conducting research through a qualitative approach during the fieldwork conducted for about three months, there are some conclusions related to the management of early childhood character development in this institution. The results obtained were that 1) management of early childhood character development was heavily influenced by the success of parenting or patterns of care carried out by parents during the home 2) Parenting was chosen as one of the strategies because it was judged very effective for the sustainability of child education throughout the home. 3) The obstacle that exists in the management of the development of early children's character is that the majority of pupils' guardians still have not mastered the existing parenting science.